2014
DOI: 10.1590/s0080-623420140000800009
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Vulnerability: A Case Study on intrafamilial violence, Drug Addiction and Adolescent Pregnancy

Abstract: Vulnerabilidade cumulatiVa: estudo de um caso de Violência doméstica, toxicodependência e GraVidez na adolescência Vulnerabilidad acumulada: estudio de un caso de Violencia doméstica, droGadicción y el embarazo en la adolescencia 1 phd student in clinical psychology at the institute of psychology, university of sao paulo, sao paulo, brazil. 2 master's degree in clinical psychology from the institute of psychology, university of sao paulo, sao paulo, brazil. 3 master's student in clinical psychology at the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…23 A study carried out with 881 adolescents in Mexico points out the relation between alcohol consumption and other drugs by adolescents in situations of violence. 24 It is emphasized that adolescent drug use is seen as an "exit" from the experience of violent acts, increasing the possibility of consuming other psychoactive substances.…”
Section: Repercussions Of Conjugal Violencementioning
confidence: 99%
“…23 A study carried out with 881 adolescents in Mexico points out the relation between alcohol consumption and other drugs by adolescents in situations of violence. 24 It is emphasized that adolescent drug use is seen as an "exit" from the experience of violent acts, increasing the possibility of consuming other psychoactive substances.…”
Section: Repercussions Of Conjugal Violencementioning
confidence: 99%
“…20 Refuge means to say that there is a hidden force or power that makes them continue life. However the streets expose them to drugs and prostitution, and drugs as well as being harmful to health, 21 do not alleviate the suffering caused by the abusive experience and further intensify other health issues.…”
Section: Discussionmentioning
confidence: 99%
“…They remember their use by their parents and they used them as well. Studies show that situations of vulnerability such as these is common amongst pregnant teenagers who are victims of violence and drug abuse 19 . Other studies have shown relations between the and abuse of alcohol and other drugs in a person's childhood and the experience of situations of intra-family violence and domestic abuse in marriages 7,8 .…”
Section: The Use Of Alcohol and Other Drugs By Family Member And The mentioning
confidence: 99%
“…In adolescence, physical violence was highlighted by both sexes (78.3% girls and 57.8% boys), followed by negligence for boys (15.2%) and sexual violence for girls (33.9%) 15 . Studies with pregnant adolescents or teenage mothers that went through situations which involved intra-family violence, showed significant failures in the process of emotional maturity, affecting the physical and psychological health of teenagers with reference to their baby and consequently the bonding process between the mother and baby [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%